Economic burden of avoidable blindness due to diabetic macular edema in Ecuador - Lucio, Ruth; Teran, Juan Antonio; Luque, Paula (Frontiers in Public Health, 2025)
IntroductionIn Ecuador, the economic burden of diabetes-related visual impairment has not been studied cohesively. More evidence—that takes into account lost productivity, direct costs, and intangible costs—is required to support public policies that prevent and treat diabetes-related visual impairment.ObjectiveThe purpose of this research is to estimate the economic burden of avoidable blindness due to diabetic macular edema in Ecuador.MethodsCosts were estimated in a one-year, retrospective, cost-of-illness study focusing on two groups of people. The first group contains those that have become blind because of a lack of timely medical treatment for diabetic retinopathy (DR) and diabetic macular edema (DME). The second group contains those that could avoid blindness by receiving timely treatment. Productivity costs are costs associated with lost ability to work due to death, and with impaired (or lost) ability to work or to engage in leisure activities due to morbidity. Direct costs include direct healthcare costs and direct non-healthcare costs, i.e., costs incurred by patients and caregivers in the complete treatment of the disease. Intangible costs are a conceptual cost-compound which takes into account psychological aspects of disease such as anxiety/distress, and stigmatization.ResultsIn the year 2023, treating blindness caused by diabetic retinopathy and diabetic macular edema represents a yearly expense of USD 259.7 million—92.4% can be attributed to productivity costs. Preventing blindness caused by diabetic retinopathy and diabetic macular edema represents a yearly expense of USD 108.5 million—73.8% corresponds to costs of resources used in interventions for health promotion and disease prevention, only 26.2% corresponds to medical treatment. The difference between these two scenarios is 151.2 million; in other words, the cost of treating a person that has become disabled costs USD 33,518.98 more per year than trying to prevent the disability.ConclusionThe cost to society of providing timely treatment for diabetic retinopathy and diabetic macular edema is significantly less than the cost of supporting a person that has become blind due to lack of treatment. Thus, it would be prudent to invest in public policies that prevent and treat diabetes-related visual impairment.